Hospitality in wild places. Issue 2 (1st June 2018) - Varley, Peter; Farkic, Jelena; Carnicelli, Sandro
We contribute to the hospitality work research agenda by reconsidering the role of outdoor adventure guides as agents of hospitality, set against a conceptual backdrop of deepening ontological insecurity in industrialized societies. We argue that the concepts of dwelling, communitas and hygge have much to offer in the delivery of outdoor hospitality in general, and in outdoor adventure tourism scenarios in particular. Although originating from the Danes and their ideas of 'cosy indoor life', the concept of hygge has recently gained global attention in the debates around creating comfortable atmospheres at home, and in fostering people's emotional well-being on holiday. Moving the concept along, we suggest the stimulation of hygge in the outdoors, along with provision of the space to dwell and the stage management of the communal effervescence of communitas as part of the crucial skill set for the outdoor guide. We opine that such conceptualization can greatly inform our understanding of both the role of the outdoor guide and of the dynamics of deliverable hospitable experience more generally.